Benefit sharing from hydropower watersheds: Rationales, practices, and potential - Louis Lebel (2018)
© 2014 Elsevier B.V. Hydropower dams typically produce benefits for their developers. At the same time, large dams have various negative environmental and social consequences, in particular, upon those who must be resettled or whose livelihoods are disrupted. The anticipated and actual revenue earned by hydropower plants from the production and sale of electricity could be shared with residents of hydropower watersheds, to help offset these adverse impacts of construction and operation. The purpose of this paper is to examine the different ways in which such benefits have been shared in the Sirikit Dam hydropower watershed in Northern Thailand. Four different models for benefit sharing, each with a history in the case study site, were identified: compensation for resettlement; corporate social responsibility; community development funds; and payments for ecosystem services. The earliest program on resettlement was of limited effectiveness, because short-term compensation was insufficient to improve livelihoods or alleviate poverty. The corporate social responsibility program has been ad hoc, with achievements not always geared toward priority needs. The recently launched Power Development Fund is a promising framework, as it involves long-term sharing of revenues from the sale of electricity for projects proposed by local communities and agencies. A pilot exploration of watershed fund, based on payments for ecosystem services concepts, looked likely to falter from lack of interests among potential buyers and other institutional barriers. The case study demonstrates that different benefit sharing models have their merits and limitations which vary as a project matures - a lesson important for the Mekong Region.